2016
DOI: 10.1136/sextrans-2016-052681
|View full text |Cite
|
Sign up to set email alerts
|

Robust pro-inflammatory immune response is associated with serological cure in patients with syphilis: an observational study

Abstract: We showed that robust host pro-inflammatory immune response to infection may be the predictive factor of serological cure. The treatment outcome may be also associated with the magnitude of immune reaction occurring during the treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…A diagnosis of syphilis in humans and animal models is typically characterized by elevations in both plasma pro-inflammatory (TNFα, IFNγ, CCL4, IP-10) and anti-inflammatory cytokines (IL-10) [ 11 18 ]. This immunological profile however varies according to a number of parameters including stage of syphilis [ 4 , 17 20 ], HIV-infection status [ 20 ] and the number of previous episodes of syphilis [ 4 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…A diagnosis of syphilis in humans and animal models is typically characterized by elevations in both plasma pro-inflammatory (TNFα, IFNγ, CCL4, IP-10) and anti-inflammatory cytokines (IL-10) [ 11 18 ]. This immunological profile however varies according to a number of parameters including stage of syphilis [ 4 , 17 20 ], HIV-infection status [ 20 ] and the number of previous episodes of syphilis [ 4 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…After treatment, titres generally decline and in most immunocompetent individuals become nonreactive within 6 months. However, up to 20% of syphilis-infected individuals have a persistently reactive (albeit low-titre) NTT even after treatment, possibly related to a less robust pro-inflammatory immune response 135 . These patients are labelled as having a serofast status and are observed more commonly with treatment for late latent than early syphilis 37,136 .…”
Section: Diagnosis Screening and Preventionmentioning
confidence: 99%
“…10 A robust pro-inflammatory response may facilitate the clearance of T. pallidum. 11 Numerous studies have revealed the role of the inflammasome in regulating autophagy. 12,13 However, whether the NLRP3 inflammasome, which could mediate pro-inflammatory cytokine release, plays a regulatory mechanism in autophagy, phagocytosis and clearance after phagocytosis in macrophages during early syphilis remains unclear.…”
Section: Introductionmentioning
confidence: 99%